2007
DOI: 10.1002/pds.1399
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for submitting adverse event reports for publication

Abstract: Publication of case reports describing suspected adverse effects of drugs and medical products that include herbal and complementary medicines, vaccines, and other biologicals and devices is important for postmarketing surveillance. Publication lends credence to important signals raised in these adverse event reports. Unfortunately, deficiencies in vital information in published cases can often limit the value of such reports by failing to provide sufficient details for either (i) a differential diagnosis or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…54 Recently, an international Task Force on behalf of the International Society for Pharmacoepidemiology and the International Society of Pharmacovigilance developed guidelines based upon the validated work of Naranjo that includes all the elements ''required'' in constructing an ADR report for publication. 58 Although in the majority of the reviewed cases the suspected offending drug was withdrawn (dechallenge), spontaneous resolution with any additional systemic therapy was reached in fewer than 50% of cases, CDR testing protocol was performed in about 10%, while the Naranjo algorithm was carried out in fewer than 4%. In addition, only very few cases (13 [25%]) did not report any concurrent medications.…”
Section: Discussionmentioning
confidence: 99%
“…54 Recently, an international Task Force on behalf of the International Society for Pharmacoepidemiology and the International Society of Pharmacovigilance developed guidelines based upon the validated work of Naranjo that includes all the elements ''required'' in constructing an ADR report for publication. 58 Although in the majority of the reviewed cases the suspected offending drug was withdrawn (dechallenge), spontaneous resolution with any additional systemic therapy was reached in fewer than 50% of cases, CDR testing protocol was performed in about 10%, while the Naranjo algorithm was carried out in fewer than 4%. In addition, only very few cases (13 [25%]) did not report any concurrent medications.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the case reports revealed that the case reports followed most of the criteria mentioned by the ISoP/ ISPE 5. However, in few reports the dosage and the patient disposition were not mentioned properly.…”
Section: Discussionmentioning
confidence: 99%
“…The Erice Declaration on Communicating Drug Safety Information, published in 1997, provides a vision of vigorous, open, ethical patient-centered communications on drug safety 4. Recently, the International Society of Pharmacovigilance (ISoP) and International Society of Pharmacoepidemiology (ISPE) has developed guidelines for submitting adverse event reports for publication 5. This guideline provides the minimum criteria required in a scientific publication related to individual case reports.…”
Section: Introductionmentioning
confidence: 99%
“…1 Common processing strategy used by clinicians when assessing serious adverse events information which reduce the total amount of information processed [19]. Ultimately, if the goal is to produce better quality safety data from clinical trials [20][21][22][23], this is clearly an issue that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%